STUDY RE-ANALYSIS OF HIGH WAVE DEFORMATION IN RE-DESIGN COASTAL REVETMENT PROTECTION OF RAJABASA BEACH KALIANDA - Fauzi, Muhammad Aldhiansyah Rifqi; Mardika, Muhammad Gilang Indra; Fatkhurrozi, Muhammad; Martino, Ahmad Fadlun Harianto (Journal of Science and Applicative Technology, 2024)
The eruption of Mount Krakatau in 2018, along with high waves, has impacted the coastal conditions of Kalianda Beach. The parameters for planning the revetment include significant wave height, highest high water level (HHWL), refraction and shoaling coefficients, wave set-up, and SLR. Wave data processing was conducted using the FT Type I. The extreme wave 50-year period has a height (Hr) of 2.22 m and a period (Tr) of 14.67 s. The wave transformation coefficients for refraction and shoaling, which are 0.74 and 1.44 respectively, lead to a deformation wave height of 2.19 m at a depth of 5 m. Admiralty tide analysis yielded a tidal range element at MSL of 0.94 m, which serves as the datum for elevation point 0. The HHWL from MSL is 0.73 m, wave set-up is 0.58 m due to breaking waves at 3.43 m, and SLR is 0.16 m, leading to a DWL of 1.46 m. The wave run-up varies according to the type of revetment, boulder type elevations id 4.60 m, tetrapod type is 3.80 m, and dolos type is 4.40 m. Differences elevation are attributed to different wave run-up every type of revetment material, run-up of the type material boulder is 2.83 m, run-up of tetrapod is 2.08 m, and dolos is 2.67 m.